2016
DOI: 10.1002/mabi.201600118
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Vine Plants against Esca Disease by Breathable Electrospun Antifungal Nonwovens

Abstract: The harmful Esca disease in vine plants caused by wood-inhabiting fungi including Phaeomoniella chlamydospora (Pch) is spreading all across the world. This disease leads to poor vine crops and a slow decline or to a sudden dieback of the vine plants. The pruning wounds of vine plants are the main entry point for Pch. While model experiments with aerosol particles recommend electrospun nonwovens as a suitable barrier to block Pch, tests with living spores show clearly that only electrospun fibrous nonwovens do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…However, physical blocking has proven unsatisfactory and the inclusion of a component with antifungal activity has been put forward. Therefore, one recent report has been published on the use of electrospun materials from poly(lactide- co -glycolide) and poly(butyleneadipate- co -terephthalate), and it incorporated an antifungal agent, polyhexamethylene guanidine, as bandages to prevent esca disease by blocking the penetration of P. chlamydospora spores [ 16 ]. In addition, the fibrous membranes prepared by electrospinning enable air and moisture permeation, allowing a plant wound to “breathe”.…”
Section: Introductionmentioning
confidence: 99%
“…However, physical blocking has proven unsatisfactory and the inclusion of a component with antifungal activity has been put forward. Therefore, one recent report has been published on the use of electrospun materials from poly(lactide- co -glycolide) and poly(butyleneadipate- co -terephthalate), and it incorporated an antifungal agent, polyhexamethylene guanidine, as bandages to prevent esca disease by blocking the penetration of P. chlamydospora spores [ 16 ]. In addition, the fibrous membranes prepared by electrospinning enable air and moisture permeation, allowing a plant wound to “breathe”.…”
Section: Introductionmentioning
confidence: 99%
“…Another biological material well-known for its good mechanical properties is the mycelium of different fungi. Usually, reports about fungicide properties of diverse nanofiber mats can be found in the scientific literature dealing with nanofiber mats and mentioning fungi [21,22,23,24,25]. Only very few studies investigate interactions between fungi and nanofiber mats in which the fungi grow on polymeric material.…”
Section: Introductionmentioning
confidence: 99%
“…Materials consisting of rayon membranes on which electrospun nanofibers of soy protein/polyvinyl alcohol and soy protein/polycaprolactone are deposited have been proposed for physically blocking fungal spore penetration [7]. It has been reported that the physical blocking is insufficient, and the inclusion of an antifungal component has been put forward [8]. The proposed materials consist of lactide/glycolide copolymer and poly(butyleneadipate- co -terephthalate) blended with a specially synthesized antifungal polymer–polyhexamethylene guanidine.…”
Section: Introductionmentioning
confidence: 99%